ALIGNING TEACHING PRACTICES WITH MODERN PARENTAL DEMANDS IN MALAYSIAN CHILDCARE CENTRES - NURUL HUDA MOHD FAUZI; MOHD NAZRI ABDUL RAHMAN (P3I UMSurabaya, 2025)
This study investigates the implementation of teaching and learning approaches for infants and toddlers in Malaysian childcare centres (TASKA) and their alignment with parents’ expectations. The research was conducted using a qualitative design through a semi-structured interview with a TASKA teacher to explore daily practices, parental aspirations, and challenges faced by educators. Findings revealed that teachers frequently apply play-based and sensory learning methods, such as storytelling and interactive activities, to support children’s cognitive and emotional development. However, issues such as limited resources, large child-to-teacher ratios, and differing parental expectations present ongoing challenges. The study concludes that while current teaching strategies in TASKA reflect parental demands and promote holistic growth, continuous adaptation, teacher training, and stronger parent-teacher collaboration are essential to sustain high-quality early childhood education in Malaysia.